Urgensi Bela Negara Untuk Meningkatkan Jiwa Nasionalisme Dan Perananya Dalam Intergrasi Nasional - Rasona Sunara Akbar; M. Bayu Krisna Aji; M Farhan Zaqi Zhilal; Denisa Aurora; Lalu Muhammad Ferry Akbar; Anandhita Khusnul Khotimah; Dendis Zain Rozansyah; Faiz Ragachdo (Journal on Education, 2024)
This research aims to provide a deeper understanding of the urgency of the concept of National Defense in strengthening national identity and increasing the feeling of love for the country among the community. Apart from that, this research also aims to analyze the role and implementation of the National Defense program in the context of national integration, by identifying factors that support or hinder its success. This research uses a qualitative descriptive approach to explore the concepts of National Defense, the spirit of nationalism, and national integration and to identify the relationship between the three. The concept of National Defense has high urgency in the context of national development in Indonesia. Through active community participation in National Defense programs, a collective awareness of the importance of loyalty, solidarity and national unity is created. Defending the Nation has a significant impact on increasing the spirit of nationalism among society. Through participation in National Defense activities, society can strengthen feelings of love and loyalty towards the homeland and foster solidarity and unity among citizens. Implementation of National Defense programs also has a positive impact in strengthening national integration. Through collaboration between citizens from various backgrounds, an inclusive and harmonious environment is created amidst cultural and ethnic diversity.